First analysis of ancient burned human skeletal remains probed by neutron and optical vibrational spectroscopy - Festa, G. (2019)
Burned skeletal remains are abundant in archaeological and paleontological sites, the result of fire or of ancient funerary practices. In the burning process, the bone matrix suffers structural and dimensional changes that interfere with the reliability of available osteometric methods. Recent studies showed that these macroscopic changes are accompanied by microscopic variations are reflected in vibrational spectra. An innovative integrated approach to the study of archaeological combusted skeletal remains is reported here, where the application of complementary vibrational spectroscopic techniques-INS (inelastic neutron scattering), FTIR (Fourier transform infrared), and micro-Raman-enables access to the complete vibrational profile and constitutes the first application of neutron spectroscopy to ancient bones. Comparison with data from modern human bones that were subjected to controlled burning allowed identification of specific heating conditions. This pioneering study provides archaeologists and anthropologists with relevant information on past civilizations, including regarding funerary, burial, and cooking practices and environmental settings.